2021
DOI: 10.3389/fmed.2021.680602
|View full text |Cite
|
Sign up to set email alerts
|

Empty Sella Syndrome as a Window Into the Neuroprotective Effects of Prolactin

Abstract: Background: The goal of this study was to relate diffusion MR measures of white matter integrity of the retinofugal visual pathway with prolactin levels in a patient with downward herniation of the optic chiasm secondary to medical treatment of a prolactinoma.Methods: A 36-year-old woman with a prolactinoma presented with progressive bilateral visual field defects 9 years after initial diagnosis and medical treatment. She was diagnosed with empty-sella syndrome and instructed to stop cabergoline. Hormone testi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…These studies attribute increased oligodendrocyte proliferation and remyelination after injury to increased PRL levels [ 8 ] and increased white matter volume [ 10 ]. We have previously shown that remyelination is possible after compressive injuries to the anterior visual pathway [ 22 ] and that measures of diffusion known to correlate with myelination are sensitive to varying levels of serum prolactin in a patient with empty-sella syndrome [ 7 ]. Due to PRL’s role in remyelination, this provides another possible mechanism for its protective quality following compressive injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies attribute increased oligodendrocyte proliferation and remyelination after injury to increased PRL levels [ 8 ] and increased white matter volume [ 10 ]. We have previously shown that remyelination is possible after compressive injuries to the anterior visual pathway [ 22 ] and that measures of diffusion known to correlate with myelination are sensitive to varying levels of serum prolactin in a patient with empty-sella syndrome [ 7 ]. Due to PRL’s role in remyelination, this provides another possible mechanism for its protective quality following compressive injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative RNFL measurements have also been shown to predict post-operative visual outcomes for pituitary tumor patients [ 6 ]. These measurements may serve as biomarkers for injury along the visual pathway where thinning indicates ongoing injury and disease progression [ 7 , 24 ]. This allows for RNFL measurements to be used to quantify the efficacy of neuroprotective agents, like PRL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also underlie findings that in females with secondary progressive MS treated with domperidone, subjects with higher prolactin levels had reduced disease progression [51]. Prolactin may be generally protective of white matter health [52], and elevated circulating levels of prolactin during sleep have been proposed as potentially mediating the enhanced levels of remyelination during sleep compared to during wakefulness [53,54]. One of the well-known effects of KOR agonists in vivo is to cause significant and reliable increases in circulating prolactin following release from pituitary lactotroph cells.…”
Section: Mechanism For Kor Agonist Effects On Ms Models and Remyelina...mentioning
confidence: 98%